Animal Quartet Card Learning Media: How Does It Influence Students' Science Literacy Competence? - Sayuti, Mardiana (Jurnal Pendidikan Profesi Guru, 2024)
Learning media is a very important aspect to help achieve learning goals. This research aims to examine the influence of Animal Quartet media on students' scientific literacy competencies. This research uses quantitative research methods with a one sample pretest and posttest group experimental questionnaire design with a sample size of 30 class X students at Madrasah Aliyah. Quantitative data was obtained from the average learning outcomes of students using the animal science material science literacy test instrument. Quantitative data is processed using descriptive analysis to determine the average, student learning outcomes before and after learning using Animal Quartet. The instrument used was the PISA scientific literacy test instrument with a reliability of 0.724. The research results show that the Animal Quartet Card learning media obtained an N-gain score of 0.89 which is in the high category. Then the N-gain percentage results were obtained at 89.86% which shows the effective category. So it can be concluded that after implementing the Animal Quartet Card learning media, there was a significant and effective difference in increasing students' scientific literacy competency.